Metode Beneish Ratio Index dalam Pendeteksian Financial Statement Fraud (Sudi Kasus Perusahaan Konsumsi di Bursa Efek Indonesia) - Henny Triastuti Kurnianingsih; Mitha Alvionita Siregar (Universitas Islam Islam Sumatera Utara, 2019)
The research aims to analyse and explain: 1) The percentage of consumption companies listed on the Indonesia Stock Exchange in 2016-2017, classified as manipulator; 2) The percentage of consumption companies listed on the Indonesia Stock Exchange in 2016-2017, classified as non-manipulator; 3) The percentage of consumption companies listed on the Indonesia Stock Exchange in 2016-2017 which belongs to grey company. The population in this study was 42 consumption companies listed on the Indonesia Stock Exchange in 2016-2017. Sample collection techniques using the purposive sampling method. Data collection techniques using documentation techniques. The data analysis technique used is quantitative descriptive analysis using the Beneish Ratio Index. The results of this research are: 1) Companies of consumption that are categorized as manipulator in 2016 as many as 2 companies or 9.52% and year 2017 as many as 2 companies or 9.52%. 2) Consumption companies classified as non manipulator in the year 2016 as much as 19 companies or 90.48% and 2017 as many as 17 companies or 80.95%. 3) The company of consumption which belongs to grey company in the year 2016 there is no company that belongs to Grey company and year 2017 as many as 2 companies or 9.52%.